Finite‐time extended state observer‐based exact tracking control of an unmanned surface vehicle - Wang, Ning; Zhu, Zhongben; Qin, Hongde; Deng, Zhongchao; Sun, Yanchao (International journal of robust and nonlinear control, 2021)
In the presence of complex unknowns consisting of system dynamics and environmental disturbances, it is rather meaningful to exactly track an unmanned surface vehicle (USV) to the desired trajectory in practical scenarios including routing inspection, marine survey, and guard patrol, etc. In this paper, the exact trajectory tracking problem is solved by establishing a finite‐time extended state observer‐ (FESO) based exact tracking control (FESO‐ETC) scheme. By virtue of nonsmooth analysis, the FESO is firstly devised by only requiring continuous differentiability and is incorporated into the nonsingular fast terminal sliding mode control framework, and thereby further enhancing disturbance rejection and tracking accuracy. Moreover, global finite‐time stability of the entire FESO‐ETC closed‐loop system is derived from rigorously theoretical analysis, and thereby contributing to a model‐free finite‐time control paradigm. Simulation studies and comparisons demonstrate that the proposed FESO‐ETC approach can achieve exact trajectory tracking in the presence of complex unknowns.